Getting the right task to develop metacognition and self-regulated learning in early primary school - Helen Lewis (Impact: The Journal of The Chartered College of Teachers, 2020)
There is now a good deal of evidence that developing self-regulated learning (SRL) and metacognition have a positive impact on student attainment, motivation and behaviour (Quigley, Muijs and Stringer n.d). Yet it is not always clear how different tasks and activities, including how teachers approach these, might enhance or hinder the opportunities to develop these skills. When Flavell (1979) first outlined his model of metacognition, he emphasised that metacognition arises from the interplay of self, task and strategies. In addition theories of SRL such as those by Winne and Hadwin (1998); Zimmerman and Reisenberg (1997); Boekaerts and Como (2005) stress the importance of task regulation and motivation. Below we detail how in the early years, task design can facilitate or hinder the development of metacognition and SRL.